Tracing online flood conversations across borders: a watershed-level analysis of geo-social media topics during the 2021 European flood - S. Dujardin; S. Dujardin; D. Arifi; D. Arifi; S. Schmidt; S. Schmidt; C. Linard; C. Linard; B. Resch; B. Resch; B. Resch (Natural Hazards and Earth System Sciences)
In the face of rapid population growth, urbanisation, and accelerating climate change, rapid and accurate disaster detection has become critical to minimise human and material losses. In this context, geo-social media (referring to georeferenced social media posts) data have proven to be a sensible data source for tracing disaster-related conversations, especially during flood events. However, current research often neglects the relationship between information from social media posts and their corresponding geographical context. In this paper, we examine the emergence of disaster-related social media topics in relation to hydrological and socio-environmental features at the watershed level during the 2021 western European flood, while focusing on transboundary river basins. Building on an advanced machine-learning-based topic modelling approach, we show the emergence of flood-related geo-social media topics in both river-basin-specific and cross-basin contexts. Our analysis reveals distinct spatio-temporal dynamics in the public discourse, showing that timely topics describing heavy rainfall or flood damage were closely tied to immediate environmental conditions in upstream areas, while post-disaster topics about helping victims or volunteering were more prevalent in less affected areas located in both upstream and downstream areas. These findings highlight how social media responses to disasters differ spatially across watersheds and underscore the importance of integrating geo-social media analysis into disaster coordination efforts, opening new opportunities for transboundary collaborations and the coordination of emergency response along border-crossing rivers.